High-frequency homologous recombination in vaccinia virus DNA. - Ball, L A (1987)
A recombinant vaccinia virus genome was constructed in which the viral thymidine kinase (tk) gene was placed between direct repeats of a 1.5-kilobase-pair DNA sequence of heterologous origin. When forced to replicate in tk- cells in the presence of methotrexate (i.e., under tk+-selective conditions), the recombinant maintained its tk+ phenotype. Under nonselective conditions, however, the tk gene was frequently excised by both inter- and intramolecular recombination events because the repeated sequences provided substantial targets for homologous DNA recombination. Unique DNA products of intramolecular recombination were detected in the cytoplasm of infected cells soon after the onset of viral DNA replication, and their appearance was blocked by inhibitors of DNA synthesis. During repeated passage of the virus under nonselective conditions, the tk+ fraction decreased with first-order kinetics at a rate that reflected the frequency of recombination per cycle of virus replication. Eventually, a residual population of stable tk+ viruses remained, and analyses of the genome structures of individual members of this population showed that some of them appeared to be the products of nonhomologous DNA recombination.